PENGARUH FASILITAS RUANG TUNGGU TERHADAP KEPUASAN PENUMPANG BANDAR UDARA INTERNASIONAL El TARI KUPANG - Awan, Fanesa Hanoek (Fakultas Ekonomi dan Bisnis, 2022)
Air transportation at this time has become a mode of transportation that is in great demand by most people, including the lower middle class, this is because the ticket prices are relatively cheap and the travel time is very short. The problems that occur at El Tari Kupang International Airport are that the air conditioner is not cold enough and the lack of reading materials such as magazines and newspapers which result in passengers being uncomfortable with the facilities at El Tari Kupang airport. This study aims to: 1) To determine the effect of facilities on passenger satisfaction at El Tari International Airport Kupang. 2) To find out how much influence the facilities have on passenger satisfaction at El Tari Kupang International Airport. This study uses a quantitative method in which the data obtained in the form of numbers that will be calculated using SPSS. The variables in this study are waiting room facilities as the independent variable (X) and passenger satisfaction as the dependent variable (Y). The total sample used in this study was 50 respondents, of which the respondents in this study were users of the waiting room at El Tari Airport Kupang. The results of this study indicate that there is an effect of waiting room facilities (X) on passenger satisfaction (Y) at El Tari Kupang International Airport, which can be seen from the tcount 7,871 > ttable 2,010. (X) has an effect on Passenger Satisfaction (Y) at El Tari Kupang International Airport by 56.3%. This shows that the waiting room facility is an important aspect that needs to be considered and 43.7% is influenced by other variables outside of the waiting room facility.